QUALITY ASSESSMENT OF BAKPAO BUNS WITH FORTIFICATION OF CATFISH PROTEIN CONCENTRATE (Pangasius hypophthalmus) - Teddi Seftiadi Azfan; N. Ira Sari; Mery Sukmiwati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The purpose of this research was to determine the quality of buns were fortified with catfish protein concentrate. The treatments that used in this research was the addition of protein concentrate catfish which is consists of three levels B0 (without fish protein concentrate), B1 (5% fish protein concentrate), B2 (7.5% fish protein concentrate), B3 (10% fish protein concentrate ). Based on research, the effect of the fortified catfish protein concentrate on the quality of bakpao buns significantly affect the organoleptic value, water content, protein content and fat content. The results show organoleptic value of the three treatments, where the bakpao buns with fortification catfish protein concentrate 5% (B1) or 30 gram is the best treatment with apparance values 7.80, aroma values 7.88, taste values 8.73, and the texture valuesof 7:40. Based on proximate value of the three treatments, bakpao buns with fortification catfish protein concentrate 10% (B3) or 60 gram is best treatments with a water content of 26.18%, protein content 14:51%, and 3.66% fat content.Keywords: Catfish, Protein concentrate, Bakpao buns, Quality, Fortification